Relation Between Clinical Parameters and Pulmonary Function in Ankylosing Spondylitis - Dilek Durmuş,; Fırat Altay,; Oğuz Uzun,; Ferhan Cantürk, (Archives of Rheumatology, 2009)
Objective: The aim of this study was to determine pulmonary function in ankylosing spondylitis (AS) patients and to assess the relationship with clinical parameters. Material and Methods: A total of 30 patients with definite AS (Group 1) and 20 age-matched healthy controls (Group 2) were recruited for the study. Patients and healthy controls were assessed according to visual analog scale (VAS) pain, 6 minute walk test (6MWT), chest expansion, the Bath Ankylosing Spondylitis Disease Activity Index (BASDAI), and the Bath Ankylosing Spondylitis Functional Index (BASFI). Pulmonary function was assessed by forced vital capacity (FVC), forced expiratory volume in 1 second (FEV1), and vital capacity (VC). Results: There was no statistically significant difference in age or body mass index between groups (p>0.05). There were significant differences in VAS pain, chest expansion, BASDAI and BASFI scores and pulmonary function parameters FVC, FEV1, VC and 6MWT between groups (p<0.05). There were significant correlations between all pulmonary function parameters and clinical and functional measures. Conclusion: Based on these results, we conclude that there is a correlation among functional performance, pulmonary capacities and clinical parameters in AS patients. (Turk J Rheumatol 2009; 24: 178-82)